Analysis of Game-Based Learning in Improving Arabic Vocabulary Mastery in Madrasah Tsanawiyah Students - Khairani, Ismi; Lubis, Zulfahmi (STUDI ARAB, 2025)
Vocabulary mastery is a crucial aspect in learning Arabic, in practice there are still many students who have difficulty in understanding and remembering mufrodat even though the Game-Based Learning method has been applied. This research is motivated by the fact that the application of GBL in class VIII MTs Swasta Riyadussholihin Sunggal Medan has not fully succeeded in improving vocabulary mastery evenly among students. The main purpose of this study is to analyze students' and teachers' experiences in the implementation of GBL and identify the supporting and inhibiting factors that influence the success of this method. The research used a descriptive qualitative approach with a case study design. The research subjects were one Arabic teacher and all students of grade VIII, with data obtained through observation, in-depth interviews, and documentation, then analyzed using the Miles and Huberman model. The results showed that although GBL increased students' motivation and engagement, around 45% of students still experienced difficulties in vocabulary acquisition due to factors such as the fast rhythm of the game, lack of understanding of the rules, and different learning styles. This study recommends modifying the GBL strategy to be more inclusive, adaptive to the needs of students in madrasah.